RELATIONSHIP BETWEEN STATIC AND DYNAMIC DISPLACEMENTS OF STRUCTURES - Endah Wahyuni (Journal of Civil Engineering, 2010)
The relationship between the static and dynamic displacements of a structure is studied and explores the application of the relationship. The key parameters are: the static stiffness of the structure, which is a measure of its resistance to an applied load; and the dynamic stiffness, which relates to a specific mode of vibration. To illustrate the salient features, two simple examples will be considered, first a beam and second a plate. These may be considered to be simple representations of a bridge and a floor respectively. The conclusions of the research are the number of modes considered increases the difference between total modal displacement and the static displacement decreases. The first mode dominated the sumof the modal displacement. It is therefore apparent that measurements of both static and dynamic stiffness can both provide useful information on the elastic behavior of a structure.